The Hopi - Santella, Andrew (New York Children's Press, 2004)
Describes the Hopi way of life, including their villages, families, farms, and reaction to the white settlers
Includes bibliographical references (p. 44) and index
Hurg
5 8
Keywords: Hopi Indians -- History; Hopi Indians -- Social life and customs; Indians of North America -- Arizona